A teoria das emoções na psicanálise existencial sartreana - Sebastião Linhares Bezerra Júnior (2021)
The present study, focusing on Jean-Paul Sartre's thought on the relationship between the phenomenology of emotions and his project of constructing an existential psychoanalysis, questioned in the onto-phenomenological description of consciousness, the theory of emotions, and otherness, what is the justification offered by Sartre for his proposal of existentialist psychoanalysis being based on the potential practical value of a phenomenological study of the emotions, clarifying the tensions between consciousness and being, between phenomenology and ontology, as well as concepts such as Intentionality, Ego and Nadification, and the Sartrean attempt to reconcile the Em-si with the Para-si of consciousness. The proposal of this research, therefore, is to analyze the concrete human emotional constituents, in the understanding of a totality of a subject that needs to face the determinisms of the world, and the consequent Sartrean proposal of psychoanalysis to be offered to this suffering subject.